A Comparison of Cognitive and Social Presence in Online Graduate Courses: Asynchronous vs. Synchronous Modalities - Regina G. Presley; Denise M. Cumberland; Kevin Rose (Online Learning, 2023)
Over the last decade, online courses have continued to expand, and students in higher education are being offered increased access to technology and communication tools in online learning programs. This action research study analyzed the impact of two distinct types of online course instruction (100% asynchronous and weekly online synchronous meetings) on learning outcomes, including cognitive and social presence, knowledge gained, and student perceptions. Study participants consisted of graduate students enrolled in online sections of a course on program evaluation. Four sections of the course were available: two included a synchronous meeting using web-conferencing, and two used an asynchronous format. A quasi-experimental design was used and included a pre-post test knowledge assessment, a modified version of the Community of Inquiry questionnaire (CoI), and end-of-course student evaluations. The mean ratings of the CoI in this study ranged from 3.75–4.60 out of 5. There was a significant difference in the cognitive presence scores for synchronous (M=4.26, SD=.529 asynchronous (M=4.47, SD=.454) conditions; t(97)=-2.07, p =.041. Our results suggest when students learn in an asynchronous format, they have a higher cognitive presence. The average scores on the knowledge pre-test were the same for both sections but post-test scores were slightly higher in the asynchronous section. Instructor ratings were high for all courses. These findings may offer valuable implications to higher education programs that have recently transitioned to online teaching modalities.